Perception and Economic Impact of Agromet Advisory Services: A Case Study of Thrissur AICRPAM Centre of Kerala State (Indian Journal of Extension Education, 2020)
This research explored the awareness, perception and economic impact of micro-level Agromet Advisory Services (AAS) issued by All India Coordinated Research Project on Agrometeorology of Indian Council of Agricultural Research through its 25 cooperating centres located across the country. Micro-level advisory based on weather forecast is the innovative and first of its kind in the country. Studies on economic impact of these micro-level advisories were uncommon. The study was conducted using field survey to assess the perception and economic impact of micro-level AAS at Thrissur AICRPAM centre on pilot basis. Two categories viz. AAS and non-AAS farmers, consisting of 40 farmers in each category were selected through multi-stage stratified random sampling technique. The probit regression model was employed to assess the factors determining willingness to pay (WTP) for AAS. The results revealed that 55% of AAS farmers rated the advisories as ‘very good’ on the scale of very poor to very good. Non-AAS farmers lagged in both awareness and adoption of services when compared to AAS farmers. Farmers’ age, education and land holding size were found to be most important factors influencing farmer’s willingness for pay-based services. Economic impact revealed that there was increase of 19-34 percent of income for AAS farmers in comparison to non-AAS farmers.